1994
DOI: 10.1172/jci117251
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates extracellular matrix protein synthesis through induction of transforming growth factor-beta expression in rat glomerular mesangial cells.

Abstract: Angiotensin II (Ang II) has been implicated in the development of progressive glomerulosclerosis, but the precise mechanism of this effect remains unclear. In an experimental model, we have shown previously that TGF-,6 plays a key role in glomerulosclerosis by stimulating extracellular matrix protein synthesis, increasing matrix protein receptors, and altering protease /protease-inhibitor balance, thereby inhibiting matrix degradation. We hypothesized that Ang II contributes to glomerulosclerosis through induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
640
1
20

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,007 publications
(704 citation statements)
references
References 46 publications
(48 reference statements)
43
640
1
20
Order By: Relevance
“…19 In addition, a complex and rich interaction between TGF-b and the renin-angiotensin system has been observed in the kidneys of experimental animals with chronic kidney diseases. 20 Previous studies demonstrated that Ang II stimulates the synthesis of TGF-b in cultured rat vascular smooth muscle cells, 21 rat glomerular mesangial cells 22 and cultured murine proximal tubular cells. 23 In addition, blocking Ang II with ACE inhibitors or Long-term effects of HRP on 2K1C kidneys M Ryuzaki et al Ang II type 1 receptor antagonists decreased the overexpression of TGF-b in animals with chronic kidney diseases, 20 and the blocking of prorenin binding to the (P)RR by HRP inhibited the elevated Ang II levels in the kidneys of the animals with diabetes 4 and hypertension.…”
Section: Long-term Effects Of Hrp On 2k1c Kidneys M Ryuzaki Et Almentioning
confidence: 99%
“…19 In addition, a complex and rich interaction between TGF-b and the renin-angiotensin system has been observed in the kidneys of experimental animals with chronic kidney diseases. 20 Previous studies demonstrated that Ang II stimulates the synthesis of TGF-b in cultured rat vascular smooth muscle cells, 21 rat glomerular mesangial cells 22 and cultured murine proximal tubular cells. 23 In addition, blocking Ang II with ACE inhibitors or Long-term effects of HRP on 2K1C kidneys M Ryuzaki et al Ang II type 1 receptor antagonists decreased the overexpression of TGF-b in animals with chronic kidney diseases, 20 and the blocking of prorenin binding to the (P)RR by HRP inhibited the elevated Ang II levels in the kidneys of the animals with diabetes 4 and hypertension.…”
Section: Long-term Effects Of Hrp On 2k1c Kidneys M Ryuzaki Et Almentioning
confidence: 99%
“…29,33,34 The likely importance of the local glomerular RAAS relates to the pathogenesis of glomeruloscleorsis and the loss of glomerular permselectivity observed in many glomerular diseases. In cultured mesangial cells, Ang II [35][36][37] and aldosterone 38,39 provoke synthesis of extracellular matrix (ECM) proteins that accumulate in glomerulosclerosis. In podocytes, Ang II has been shown to induce apoptosis, 40,41 cytoskeletal rearrangement 42 and nephrin loss 43 in podocytes, alterations that have been linked to albuminuria.…”
Section: Intrarenal Raasmentioning
confidence: 99%
“…Numerous studies including data from our own laboratory indiStudies have provided evidence that angiotensin-converting enzyme inhibitors and angiotensin-receptor antagonists attenuate diabetic glomerulosclerosis and slow the progression of diabetic kidney disease [1, 2, cate that hyperglycemia induces an increase in TGF-β1 protein and mRNA expression in experimental and human diabetes [15,19,20,21] and in cultured mesangial cells [22,23,24]. Although previous investigations clearly demonstrated that ang II stimulates the synthesis of extracellular matrix proteins through an enhanced TGF-β1 expression in mesangial cells [25] the molecular mechanism of ang II-induced TGF-β1 gene activation, particularly the detailed localization of the ang II responsive elements on the TGF-β1 promoter, have not been studied yet.…”
mentioning
confidence: 99%